2021
DOI: 10.3389/fphar.2021.616253
|View full text |Cite
|
Sign up to set email alerts
|

Centhaquine Restores Renal Blood Flow and Protects Tissue Damage After Hemorrhagic Shock and Renal Ischemia

Abstract: Background: Centhaquine (CQ) (Lyfaquin®) is in late stage clinical development as a safe and effective first-in-class resuscitative agent for hemorrhagic shock patients (NCT02408731, NCT04056065, and NCT04045327). Acute kidney injury (AKI) is known to be associated with hemorrhagic shock. Hence, effect of CQ on protection of kidneys from damage due to hemorrhagic shock was investigated.Methods: To assess effect of CQ on AKI in shock, we created a rat model with hemorrhagic shock and AKI. Renal arteries were cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
2
3
0
Order By: Relevance
“…Analysis of kidney tissues in these rats showed significant up-regulation ( p = 0.024) of hypoxia-inducible factor 1a (HIF-1α) and reduced ( p = 0.03) mitochondrial DNA damage than control rats. We also observed reduced acute kidney injury and apoptosis in kidneys in CQ rats ( Ranjan et al, 2020 ; Ranjan et al, 2021 ). Thus, CQ, known to activate the α-adrenergic system, has proven to be an effective resuscitative agent for hypovolemic/hemorrhagic shock and potentially improves cardiovascular function, renal tissue perfusion, and protection.…”
Section: Development Of Centhaquine An α-2 Agonist As a Resuscitative...supporting
confidence: 53%
“…Analysis of kidney tissues in these rats showed significant up-regulation ( p = 0.024) of hypoxia-inducible factor 1a (HIF-1α) and reduced ( p = 0.03) mitochondrial DNA damage than control rats. We also observed reduced acute kidney injury and apoptosis in kidneys in CQ rats ( Ranjan et al, 2020 ; Ranjan et al, 2021 ). Thus, CQ, known to activate the α-adrenergic system, has proven to be an effective resuscitative agent for hypovolemic/hemorrhagic shock and potentially improves cardiovascular function, renal tissue perfusion, and protection.…”
Section: Development Of Centhaquine An α-2 Agonist As a Resuscitative...supporting
confidence: 53%
“…Moreover, analysis of kidney tissues in these rats showed significant up-regulation (p=0.024) of hypoxia inducible factor 1 (HIF-1). We also observed down-regulation of early acute kidney injury and apoptotic markers after resuscitation with CQ [152,153]. Overall, these results showed that CQ is as an effective resuscitative agent with potential to improve cardiovascular function as well as renal tissue perfusion and protection after hemorrhagic shock.…”
Section: Regulation Of Blood Pressure After Hemorrhagic Shocksupporting
confidence: 58%
“…Considering that venous endothelial cells are less thrombogenic than arterial endothelial cells [ 47 ], centhaquine, as a pure venoconstrictor (α2B-adrenoreceptors), may maintain a steady flow and no or minimal pulsatility in veins [ 48 , 49 ], thus exploiting the beneficial anti-thrombogenic profile of venous endothelial cells [ 47 ] without directly affecting the arterial side of the circulation [ 41 ]. Moreover, its action on central α2A-adrenoreceptors facilitates arteriolar flow and tissue perfusion, which enhances organ protection during severe hemorrhage [ 50 , 51 ]. Further research is necessary to fully clarify the effects of centhaquine at the molecular and cellular level and, ultimately, its integrative mechanism of action.…”
Section: Discussionmentioning
confidence: 99%